Development of a Basic Embroidery Technique Book Based on Storytelling for Fashion Design Education Students - Eka Rahma Dewi; Armaini Rambe; Dermawan Pakpahan; Rossy Luckita Sasmita (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
This study aims to develop a storytelling-based embroidery book for the basic embroidery techniques course to improve the creativity of fashion education students. The study uses the Research and Development (R&D) method with a 4D model that includes the define, design, develop, and disseminate stages. From the results of the validity test of material experts, media experts and student trials. The validity of the material experts obtained 83.9% and the media experts obtained 82.87% with very good criteria. The results of the small group trial obtained 82.2%, the medium scale trial obtained 85.3% and the large group trial obtained 87.3% with a very good category. The results of the study show that the storytelling-based embroidery book for the basic fashion embroidery techniques course is suitable for use in learning.